Risk factors to identify the indication for regional nodal irradiation in T1-2N1M0 breast cancer: A joint analysis of 4,243 real-world cases from two institutions - Sun, Guang-Yi; Wen, Ge; Zhang, Yu-Jing; Tang, Yu; Jing, Hao; Fang, Hui; Wang, Jian-Yang; Zhang, Jiang-Hu; Zhao, Xu-Ran; Chen, Si-Ye; Song, Yong-Wen; Jin, Jing; et al. (Frontiers in Oncology, 2022)
Purpose: To evaluate the role of regional nodal irradiation (RNI) in patients with T1-2N1M0 breast cancer and identify the subgroup that could benefit from RNI. Methods and materials: 4243 women with pT1-2N1M0 breast cancer treated at two institutions in China were retrospectively reviewed. Survival rates were calculated by the Kaplan–Meier method and compared by log-rank test. The association of risk factors with survival outcomes was evaluated using multivariable proportional hazards regression. Results: 932 patients (22.0%) received RNI. At a median follow-up of 5.9 years, the 5-year locoregional recurrence (LRR), distant metastasis (DM), disease-free survival (DFS), and overall survival (OS) rates were 4.0% and 7.2% (P = .001), 13.2% and 10.6% (P = .465), 85.0% and 84.7% (P = .131), and 93.9% and 92.8% (P = .004) in the RNI and non-RNI groups, respectively. Multivariate analysis revealed that RNI was an independent prognostic factor for lower LRR (P = .001) and longer DFS (P = .013). Patients were stratified into low-, intermediate-, and high-risk groups based on eight non-therapeutic risk factors. RNI significantly decreased the 5-year LRR (2.2% vs. 7.0%, P = .001) and improved the 5-year DFS (88.8% vs. 84.9%, P = .015) and OS (95.8% vs. 93.9%, P = .010) in the intermediate-risk group. However, neither low-risk group nor high-risk group had survival benefit from RNI. Conclusion: T1-2N1M0 breast cancer is a heterogeneous disease. We found that RNI only improved survival in the intermediate-risk group. It might be omitted in low-risk patients, and the role of RNI in high-risk patients needs further study.